Kesiapan Otoritas Pelabuhan Teluk Bayur Menghadapi Era Kapal Otonom (Maritime Autonomous Surface Ship/MASS) - Wirza, Elfira; Mashartanto, Achmad Ali; Silen, Adhi Pratistha (Jayapangus Press, 2025)
The development of autonomous ships signifies progress in the application of information and communication technology within the marine transportation industry. The readiness of various supporting aspects, such as ports, must accompany the operation of autonomous ships. As a maritime nation with numerous ports, Indonesia must begin to prepare for the changes in the maritime industry resulting from technological advancements that support autonomous ship operations. Teluk Bayur Port in West Sumatra, one of the ports in Indonesia, must be equipped to adapt to these changes. A crucial aspect of this preparation is the ability of the port authority and its employees to adjust to the impacts of technology implementation. This study aims to evaluate the readiness level of the port authority and its employees to adapt to the operations of autonomous ships. The research includes a survey conducted through the distribution of questionnaires, which are analyzed using descriptive statistical methods, measuring both organizational readiness and port authority employee readiness variables. Employee readiness is assessed through three indicators, while organizational readiness is evaluated through seven indicators. The results indicate that the average employee readiness score is good at 4.14, and organizational readiness is also satisfactory at 3.96, both in adapting to the changes brought about by technological advancements regarding autonomous ships. Despite both variables' overall positive average scores, several indicators require improvement. For employee readiness, there is a need to enhance knowledge about autonomous ships and the ability to prevent cybercrime. For organizational readiness, improvements should focus on organizational management, the quality of human resources, ICT facilities and infrastructure, and financial aspects.